Simulação numérica de uma Antena Ressoadora Dielétrica (DRA) baseada em si, ag e grafeno para aplicações em espectro thz - SANTOS, Marcos Gabriel Fernandes dos (2023)
In this work, the study of the radiation characteristics of two antennas with graphene layers, constituted of silicon and silver components, operating in the terahertz band is carried out. Both antennas are devices integrated with graphene nano-disk for dy- namic control of frequency responses, obtaining enhanced performance by modifying specific components and subcomponents. The first antenna model operating in the 3.27 to 3.31 THz frequency range has a surface called Non-Resonant Microstrip Patch (NMP) which is responsible for operating as a response electromagnetic mode selector surface. Similarly, the second antenna model consists of a cylindrical dielectric resonator, however, it is an antenna which was designed by a unique method aiming at smaller scale subcomponents and high bandwidth, being able to operate in different frequency ranges due to graphene, this model operates in the frequency range of 7.24 - 7.27 THz. When considering the temperature variation of the graphene nanodisk and keeping the chemical gate values of this material fixed, negligible changes occur in the way the antenna has its frequency response control. It is shown that the first antenna model operates with efficiency of around 84%, while the second antenna model presented much higher return loss and bandwidth results, reaching a reflection coefficient of -54.9501 dB and bandwidth of 0.35 THz. If the models are compared, it is possible to verify that the first antenna model obtained a better radiation efficiency value, however, the second model presented greater proximity to physical prototypes, obtaining better impedance matching and consequently greater efficiency as an antenna.